Genome-Wide Association Study of Pericarp Color in Rice Using Different Germplasm and Phenotyping Methods Reveals Different Genetic Architectures - Yang, Wu; Chen, Luo; Zhao, Junliang; Wang, Jian; Li, Wenhui; Yang, Tifeng; Dong, Jingfang; Ma, Yamei; Zhou, Lian; Chen, Jiansong; Wu, Wei; Zhang, Shaohong; et al. (Frontiers in Plant Science, 2022)
Pericarp colors (PC) in rice are determined by the types and content of flavonoids in the pericarp. The flavonoid compounds have strong antioxidant activities and are beneficial to human health. However, the genetic basis of PC in rice is still not well-understood. In this study, a genome-wide association study (GWAS) of PC was performed in a diverse rice collection consisting of 442 accessions using different phenotyping methods in two locations over 2 years. In the whole population consisting of white and colored pericarp rice, a total of 11 quantitative trait loci (QTLs) were identified using two phenotyping methods. Among these QTLs, nine were identified using the phenotypes represented by the presence and absence of pigmentation in pericarp, while 10 were identified using phenotypes of the degree of PC (DPC), in which eight are common QTLs identified using the two phenotyping methods. Using colored rice accessions and phenotypes based on DPC, four QTLs were identified, and they were totally different from the QTLs identified using the whole population, suggesting the masking effects of major genes on minor genes. Compared with the previous studies, 10 out of the 15 QTLs are first reported in this study. Based on the differential expression analysis of the predicted genes within the QTL region by both RNA-seq and real-time PCR (RT-PCR) and the gene functions in previous studies, LOC_Os01g49830, encoding a RAV transcription factor was considered as the candidate gene underlying qPC-1, a novel QTL with a large effect in this study. Our results provide a new insight into the genetic basis of PC in rice and contribute to developing the value-added rice with optimized flavonoid content through molecular breeding.